5 major achievements of the Sustainable Land Use Systems (SLUS) Project in Colombia - Vanegas Cubillos, Martha Cristina; Villarino, Maria Eliza J.; Castro-Nuñez, Augusto (2023)
The SLUS Project has been generated evidence on the links between climate action and peacebuilding. During its implementation, four tools have been developed, enhanced spaces for zero-deforestation dialogues in conflict-affected areas that contributed to capacity building for sustainable agricultural production and research.